2021
DOI: 10.21203/rs.3.rs-956676/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Synthesis and Future Research Directions for Tropical Mountain Ecosystem Restoration

Abstract: Many tropical mountain ecosystems (TME) are severely disturbed, requiring ecological restoration to recover biodiversity and ecosystem functions. However, the extent of restoration efforts across TMEs is not known due to the lack of syntheses on ecological restoration research. Here, based on a systematic review, we identify geographical and thematic research gaps, compare restoration interventions, and consolidate enabling factors and barriers of restoration success. We find that restoration research outside … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Although our mapping exercise revealed that the information in a given publication often informed multiple barriers, pathways for action and action lines of the UNDER strategy, a few distinct information gaps were identified, specifically related to three action lines within the Technical Capacity Pathway: (1) long‐term research, (2) monitoring, and (3) sustaining restoration. Collectively, these gaps reflect previous findings highlighting that long‐term monitoring is notably missing from ecosystem restoration projects and that most ecosystem restoration research is biased toward small‐scale and short‐lived projects, thus hampering long‐term sustainability and social learning (Wortley et al 2013; Cooke et al 2019; Christmann & Menor 2021). This is a fundamental challenge that needs to be addressed in the context of the UNDER.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although our mapping exercise revealed that the information in a given publication often informed multiple barriers, pathways for action and action lines of the UNDER strategy, a few distinct information gaps were identified, specifically related to three action lines within the Technical Capacity Pathway: (1) long‐term research, (2) monitoring, and (3) sustaining restoration. Collectively, these gaps reflect previous findings highlighting that long‐term monitoring is notably missing from ecosystem restoration projects and that most ecosystem restoration research is biased toward small‐scale and short‐lived projects, thus hampering long‐term sustainability and social learning (Wortley et al 2013; Cooke et al 2019; Christmann & Menor 2021). This is a fundamental challenge that needs to be addressed in the context of the UNDER.…”
Section: Discussionmentioning
confidence: 57%
“…Another important finding in our assessment was the large number of publications focused on forest ecosystems at the expense of grassland, dryland and mangrove ecosystems, underscoring the need for enhanced focus on restoring these as suggested elsewhere (Buisson et al 2020; Dudley et al 2020; Farrar et al 2020). A recent bibliometric analysis by Guan et al (2019) on ecosystem restoration also showed that forests are overrepresented, while a review on tropical montane restoration reported that grasslands were disproportionally underrepresented in comparison to forest ecosystems (Christmann & Menor 2021). Although tree planting is perceived as an effective strategy to mitigate atmospheric climate change (Bastin et al 2019; Busch et al 2019), native grasslands and mangrove ecosystems are also significant carbon sinks.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, restoration studies across the tropics are biased toward certain biomes and regions, and few occur across large spatial or temporal scales (Christmann & Menor, 2021). Findings from such studies are therefore site‐specific and context‐dependent, limiting the extent to which their findings apply to restoration initiatives more widely.…”
Section: Young Visions For Tropical Restoration Science For the Un De...mentioning
confidence: 99%
“…Most of the studies come from low and mid‐altitude humid forests in the neotropics (≈1,400 m) (Holl & Zahawi 2018), wherein recovery is subject to mesic abiotic conditions. In contrast, AN research in tropical ecosystems wherein recovery might be mainly hindered by abiotic limitations is incipient according to recent bibliometric analyses (Shaw et al 2020; Christmann & Menor 2021; Garibello et al 2021). Such is the case of high Andean forests (HAF; 2,600–3,500 m; Cleef 2013), wherein tree colonization and growth heavily depend on species tolerance to low temperatures and excessive solar radiation (Bader et al 2007), as well as strong winds and slow organic matter decomposition (Guariguata 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more studies are needed on the implications of tree islands in HAF. Research gaps suggest that this approach is also required globally at high‐altitude forest all along the tropical belt (Christmann & Menor 2021).…”
Section: Introductionmentioning
confidence: 99%